2023
DOI: 10.21203/rs.3.rs-2653179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivalent and Monovalent SARS-CoV-2 Variant Vaccine Boosters Improve coverage of the known Antigenic Landscape: Results of the COVID-19 Variant Immunologic Landscape (COVAIL) Trial

Abstract: Vaccine protection against COVID-19 wanes over time and has been impacted by the emergence of new variants with increasing escape of neutralization. The COVID-19 Variant Immunologic Landscape (COVAIL) randomized clinical trial (clinicaltrials.gov NCT 05289037) compares the breadth, magnitude and durability of antibody responses induced by a second COVID-19 vaccine boost with mRNA (Moderna mRNA-1273 and Pfizer-BioNTech BNT162b2), or adjuvanted recombinant protein (Sanofi CoV2 preS DTM-AS03) monovalent or bival… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our results are consistent with other reports of increased neutralization capacity of monovalent or bivalent Beta-spike-containing boosted NHPs, particularly against Omicron lineages. 40 , 41 We have shown that these boosted humoral responses are not exclusive to neutralizing antibodies. Of particular interest was the highly expanded IgA responses we observed in Beta-spike-containing formulations.…”
Section: Discussionmentioning
confidence: 86%
“…Our results are consistent with other reports of increased neutralization capacity of monovalent or bivalent Beta-spike-containing boosted NHPs, particularly against Omicron lineages. 40 , 41 We have shown that these boosted humoral responses are not exclusive to neutralizing antibodies. Of particular interest was the highly expanded IgA responses we observed in Beta-spike-containing formulations.…”
Section: Discussionmentioning
confidence: 86%
“…Residual titers plotted on the antibody landscape offer a glimpse of how well the landscape can predict titers against a particular variant. In prior antibody landscapes that use antigenic maps with BA.4/BA.5 as the latest variant, the landscapes with plotted residuals show landscapes that accurately fit antibody titers 26,50 . However, in landscapes that include XBB and BQ variants in their antigenic map, the measured titers against BA.4/BA.5 have generally been greater than what the landscape predicts 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The height of an accurate antibody landscape can be used to infer antibody titers against variants that were not used in making of the landscape 18 . It has been common for antibody landscapes generated with multiple ancestral SARS-CoV-2 vaccinations and infection histories to assume a cone landscape, often with a peak at D614G (ancestral strain) with the landscape gradually tapering as antigenic distance from D614G increases 26,28,39,48,50 . Our study found that booster vaccines or PVIs containing Omicron moderately boosted neutralizing antibodies against Omicron variants more than repeated vaccination with ancestral strain, which has been noted elsewhere 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations